Teacher Professional Development In Scientific Writing - Sitti Uswatun Hasanah; Sulha Sulha (JETL (Journal of Education, Teaching and Learning), 2022)
Teachers as professionals have very important functions, roles, and positions in achieving the vision of national education, namely creating intelligent and competitive Indonesian people. Teachers should develop their profession as a dignified profession. One form of teacher professional development is to write scientific papers, but the reality in the field is that teacher activities are still in the vision and mission of education and teaching while scientific vision and mission in the form of scientific writing and publications are often neglected. This study used a qualitative approach with a descriptive method. The research data were obtained through interviews, document analysis, participation observation, and focus group discussions. The results showed that the difficulties of teachers in writing scientific papers included: low motivation of teachers in writing, not having enough free time, lack of understanding of writing techniques, difficulties in finding data, technological stuttering, not having reference books, widespread writing services, lack of functioning of Subject Teacher Discussion (MGMP) activities in socializing writing papers, and lack of socialization from schools/institutions. The efforts that have been made by teachers to develop professionalism through writing scientific papers as a form of professional development were by: attending training/workshops, self-study, participating in competitions/tests. Based on the results of the study, it is recommended to the principal to conduct workshops on an ongoing basis, add library reference books, conduct computer training, apply a managerial reward and punishment pattern, control and monitor the implementation of MGMP and control and monitor the activities of the teacher performance appraisal team and the development team. sustainable profession.